Validation of lean manufacturing measurement instrument - Nawanir, Gusman; Lim, Kong Teong; Othman, Siti Norezam (UUM College of Business, 2015)
This study is intended to provide a valid and reliable measurement instrument for lean manufacturing practices.It is important as lack of consensus regarding the valid and comprehensive measure of lean manufacturing implementation was observed in lean manufacturing literature. 182 large and discrete process manufacturers in Indonesia were involved in this study.A structural equation modeling approach was applied to validate the instrument.The study led to the conclusion that the measurement instrument is valid and reliable.In addition, the study suggested that lean manufacturing practices should be implemented holistically and simultaneously because they are interdependent.